2021
DOI: 10.1093/cz/zoab008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lighting environment on social preferences in sticklebacks from two different photic habitats. I. mate preferences of wild-caught females

Abstract: Ultraviolet A (UVA) signals (320-400 nm) are important in mate choice in numerous species. The sensitivity for ultraviolet signals is not only assumed to be costly, but also expected to be a function of the prevailing ecological conditions. Generally, those signals are favored by selection that efficiently reach the receiver. A decisive factor for color signaling is the lighting environment, especially in aquatic habitats, as the visibility of signals, and thus costs and benefits, are instantaneously influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…The preferences of lab-bred F1 sticklebacks from both clear-water and tea-stained habitats during UV-based female-mate preference, which we tested in the present study, were largely similar to those of wild-caught females ( Hiermes et al 2021 ): an overall preference for males under UV-present conditions in the clear-water treatment ( Figure 4A, B , Table 2 , and Supplementary Table S2 ). This result points to a genetic influence on UV mate preferences.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The preferences of lab-bred F1 sticklebacks from both clear-water and tea-stained habitats during UV-based female-mate preference, which we tested in the present study, were largely similar to those of wild-caught females ( Hiermes et al 2021 ): an overall preference for males under UV-present conditions in the clear-water treatment ( Figure 4A, B , Table 2 , and Supplementary Table S2 ). This result points to a genetic influence on UV mate preferences.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, water color during the testing of preferences affected UV-based female preference of fish from tea-stained lakes even after being raised under full light spectrum conditions in clear water. In the wild-caught females ( Hiermes et al 2021 ), there were no significant water-color treatment effects as the females from both habitat types tended to prefer males under UV-present conditions in both water-color treatments. There thus may be differences in UV-preferences in the tea-stained treatment between wild-caught and F1 females that may point to an effect of developmental plasticity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, even over evolutionary timescales, fish do not always alter their signal colouration when faced with changes in light environment. For example, Hiermes et al [55] examined sticklebacks that have inhabited 'tea-stained' lakes in Scotland, which heavily absorb UV wavelengths, for more than 10 000 generations. They found that despite the low transmission of UV wavelengths in this habitat, males in tea-stained lakes still reflect UV light when reproductively active, and female sticklebacks still preferred males with UV reflectance.…”
Section: (A) Altering Signal Colouration or Visual Physiologymentioning
confidence: 99%